Middle East Conflict: Need for Credible Mediator - Michael Dorsey, James (2016)
The need for a credible universally-accepted mediator between Israelis and Palestinians has never been greater. Despite Israel’s devastating bombardment of Gaza the two sides for the first time agree on what a long-term arrangement should be. Both want a long-lasting ceasefire but need a third party to negotiate the terms.